2014
DOI: 10.1111/gcb.12663
|View full text |Cite
|
Sign up to set email alerts
|

Is climate an important driver of post‐European vegetation change in the Eastern United States?

Abstract: Many ecological phenomena combine to direct vegetation trends over time, with climate and disturbance playing prominent roles. To help decipher their relative importance during Euro-American times, we employed a unique approach whereby tree species/genera were partitioned into temperature, shade tolerance, and pyrogenicity classes and applied to comparative tree-census data. Our megadata analysis of 190 datasets determined the relative impacts of climate vs. altered disturbance regimes for various biomes acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(167 citation statements)
references
References 136 publications
9
155
1
Order By: Relevance
“…United States, synthesis of 190 tree census datasets from 50 studies comparing contemporary forests to those established before European settlement suggested that a regional increase in cool-adapted, shade-tolerant, fire-sensitive tree taxa, inconsistent with historic climate warming trends, may have resulted from fire suppression (40). Others argued, however, that high moisture during the same time period could explain the observed patterns (41).…”
Section: Observing Changes In Plant Communitiesmentioning
confidence: 99%
“…United States, synthesis of 190 tree census datasets from 50 studies comparing contemporary forests to those established before European settlement suggested that a regional increase in cool-adapted, shade-tolerant, fire-sensitive tree taxa, inconsistent with historic climate warming trends, may have resulted from fire suppression (40). Others argued, however, that high moisture during the same time period could explain the observed patterns (41).…”
Section: Observing Changes In Plant Communitiesmentioning
confidence: 99%
“…Although a large, global body of literature on climate change and forest dynamics has been developed during the last five decades (3,6,9,(11)(12)(13)(14), much of this literature provides insights on how trees respond to climate change without sufficient consideration of competition and other factors (43). Our study showed that accurately quantifying the relative contributions of both endogenous and exogenous forces simultaneously to tree demography is crucial not only for increasing our understanding of the underlying causes of the changes in forest dynamics, but also for adequately predicting the impacts of changing climates on forest dynamics.…”
Section: Significancementioning
confidence: 99%
“…Climate change models also suggest an expansion in the habitat appropriate for some oak species within the white oak group (Prasad et al, 2007). Findings from a recent study by Nowacki and Abrams (2014), in which the authors evaluated the relative influence of climate and disturbance on forest composition in the eastern U.S, suggest the dominant role of a reduced disturbance regime. A continued decline in the dominance of white oak would decrease the potential for natural regeneration of future oak forests, thus questioning whether some oak species could indeed maintain or increase dominance despite favorable climate conditions, especially in the absence of adequate disturbance.…”
Section: Continued Shift To ''Other'' Speciesmentioning
confidence: 99%